Mathematical Disposition of Students in Open-Ended Learning Based on Ethnomathematics - Ulya, Himmatul; Rahayu, Ratri (Journal of Education Technology, 2021)
Mathematical disposition plays an important role in increasing student motivation in learning mathematics. High mathematical disposition has an impact on the good learning outcomes of mathematics. This study aims to test the increase in the mathematical disposition of students who take open-ended learning based on ethnomathematics and determine the effect of mathematical disposition on students' mathematical abilities. This quantitative research refers to a one-group pretest-posttest design. Data collection techniques in this study used non-test and test techniques. The instrument used was a questionnaire to measure students 'mathematical disposition and test questions to measure students' mathematical abilities. The data analysis technique used is the gain test and regression analysis. The results of this study indicate that the mathematical disposition of students who take ethnomathematics-based open-ended learning is increased by 47%, which means that it is included in the medium category and mathematical disposition affects students' mathematical abilities through the application of open-ended learning based on ethnomathematics by 57.9%. This means that open-ended learning based on ethnomathematics can improve students' mathematical disposition.